Deionized water and acid solubility of iron in southernmost Patagonian dust samples - Cosentino, Nicolás; Ruiz-Etcheverry, Laura; Bia, Gonzalo; Simonella, Lucio; Coppo, Renata; Torre, Gabriela; Saraceno, Martín; Tur, Verónica; Gaiero, Diego (IEDA: EarthChem Library, 2020)
Abstract: Iron leaching experiments in dust samples, using deionized water and 1% nitric acid matrices. Samples from southernmost Patagonia (53.79ºS, 67.75ºW). The objective of these measurements is to characterize solubility of iron in dust samples. Other Description: Cosentino NJ, Ruiz-Etcheverry LA, Bia GL, Simonella LE, Coppo R, Torre G, Saraceno M, Tur VM and Gaiero DM (in revision) Does satellite chlorophyll-a respond to southernmost Patagonian dust? A multi-year, event-based approach. Journal of Geophysical Reseach: Biogeosciences.